PENCEMARAN TANAH OLEH Pb DAN Cd DI SEKITAR TEMPAT PEMBUANGAN AKHIR (TPA) PUTRI CEMPO, KOTA SURAKARTA - Afra Ghaida Fathassabilla; Wawan Budianta (KURVATEK, 2023)
One of the impacts of rapid population growth is the problem of waste management. One of the impacts of waste disposal at the landfill is soil contamination due to heavy metals originating from waste disposed of. This study aims to determine the concentration and distribution of heavy metals in the soil laterally and vertically around Putri Cempo Landfill through spatial analysis. Sampling was carried out at 14 points with 3 different depths, namely 10 cm, 30 cm, and 60 cm. Data analysis was performed on 42 soil samples, including analysis of grain size, pH and organic content, heavy metal content, and distribution of heavy metals. The results showed that the concentrations of Pb and Cd at the three depths of the soil samples were mostly above the background values of each heavy metal. The distribution patterns of the two heavy metals laterally in the study area were relatively different, while the vertical distribution of contaminants decreased in concentration as the distance from the soil surface increased.